Discovering the Dutch : On Culture and Society of the Netherlands - Besamusca, Emmeline; Verheul, J. (Amsterdam University Press, 2010)
"How did the Netherlands become a byword for welfare state and the "poldermodel"? What explains the fabulous political and cultural success of the Dutch Golden Age? What is the place of the Queen in a modern parliamentary democracy? Renowned Dutch scholars elucidate the complicated question of the Dutch national identity by addressing the essential themes in the country's culture, history and society. Accessibly written and charmingly illustrated, this book is both a well-balanced textbook for courses in Dutch culture and a perfect gift for all short- and long-term visitors to the Netherlands"--Provided by publisher